2013
DOI: 10.1152/ajpendo.00266.2013
|View full text |Cite
|
Sign up to set email alerts
|

Ceacam1 deletion causes vascular alterations in large vessels

Abstract: Carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) promotes hepatic insulin clearance and endothelial survival. However, its role in the morphology of macrovessels remains unknown. Mice lacking Ceacam1 (Cc1-/-) exhibit hyperinsulinemia, which causes insulin resistance and fatty liver. With increasing evidence of an association among hyperinsulinemia, fatty liver disease, and atherosclerosis, we investigated whether Cc1-/- exhibited vascular lesions in atherogenic-prone aortae. Histological ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 42 publications
(58 reference statements)
8
40
1
Order By: Relevance
“…Cells were lysed in 1% Triton-X and subjected (30 μg proteins) to immunoprecipitation at 4°C with streptavidin (Pierce). Immunoprecipitates were centrifuged and analysed by 7% SDS-PAGE and immunoblotting with 1:1000 of insulin receptor alpha (IRα) antibody (N-20; Santa Cruz, Dallas, TX, USA) or a custom-made Ab3759 polyclonal antibody against purified mouse CEACAM1, as titrated [12, 19], followed by horseradish peroxidase-conjugated mouse anti-rabbit IgG antibody (Jackson Immunoresearch, West Grove, PA, USA) and subjected to enhanced chemiluminescence (ECL; Amersham Pharmacia, Sunnyvale, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were lysed in 1% Triton-X and subjected (30 μg proteins) to immunoprecipitation at 4°C with streptavidin (Pierce). Immunoprecipitates were centrifuged and analysed by 7% SDS-PAGE and immunoblotting with 1:1000 of insulin receptor alpha (IRα) antibody (N-20; Santa Cruz, Dallas, TX, USA) or a custom-made Ab3759 polyclonal antibody against purified mouse CEACAM1, as titrated [12, 19], followed by horseradish peroxidase-conjugated mouse anti-rabbit IgG antibody (Jackson Immunoresearch, West Grove, PA, USA) and subjected to enhanced chemiluminescence (ECL; Amersham Pharmacia, Sunnyvale, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Cc1 2/2 mice (7,9), CEACAM1 endo+ mice (10), Cc1 2/2/ER mice and their wild-type (WT) littermates (C57BL/6J; The Jackson Laboratory, Bar Harbor, ME, USA), and ApoE 2/2 (B6.129P2-Apoe tm1Unc /J) mice were housed in pathogen-free conditions on a 12:12-h dark-light cycle and fed standard chow ad libitum. Cc1 2/2/ER mice were generated by cross-breeding Cc1 2/2 mice with CEACAM1 endo+ mice (endothelium-specific CEACAM1 overexpression).…”
Section: Animalsmentioning
confidence: 99%
“…En face staining for eNOS of the aortic endothelium was conducted as previously described (7). In brief, aortic fragments were fixed (4% PFA, 2 h), incubated with goat anti-eNOS antibody (1:100; 4°C, overnight) and subsequently treated with fluorescence-labeled donkey anti-goat antibody.…”
Section: Immunocytochemistry/immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Histological examination of liver section revealed that both of Ceacam1 mutants develop microsteatosis on a regular chow diet [249,250]. They also develop a pro-inflammatory state, marked by elevated tissue-associated macrophages, TNFα and IFNγ levels in liver, adipose tissue and aortae [251]. The population of hepatic CD4 + T cell was basally higher than wild type in Cc1 −/− [250], but not in L-SACC1 mice with functional inactivation of Ceacam1 in hepatocytes [249].…”
Section: Loss Of Ceacam1 Causes Fibrosing Steatohepatitis That Advancmentioning
confidence: 99%